Age Differential Effects of Severity of Visual Impairment on Mortality Among Older Adults in China. (October 2013) - Gu, Danan; Zhou, Junshan; Yong, Vanessa; Sautter, Jessica; Saito, Yasuhiko
We use a population-based longitudinal survey in China from 2002 to 2005 to examine age differentials in the association between severity of visual impairment and mortality risk in older adults. Controlling for numerous factors and baseline health, a substantial age difference is found. Young-old women and men aged 65 to 79 with severe visual impairments have 161% (hazard ratio = 2.61) and 52% (hazard ratio = 1.52) higher risk of death respectively as compared to their unimpaired counterparts. Mild impairment does not increase mortality risk among young-old adults, while both mild and severe impairment increase mortality risk by 33% and 32% for women and 24% and 34% for men among the oldest-old as a whole when all factors are controlled for. We conclude that visual impairment is an independent predictor of mortality and severe visual impairment likely plays a stronger role in determining mortality risk among young-old adults than among the oldest-old.